Financial, Governance, and Sustainability Determinants of Stock Price in an Emerging Market: Evidence from Indonesian Listed Firms - Francis Hutabarat (CV. Ulil Albab Corp, 2026)
This study examines whether financial, governance, and sustainability variables explain stock price variation in an emerging-market setting. Building on valuation theory and recent environmental, social, and governance research, the study integrates firm size, board gender diversity, profitability, shareholders’ equity ratio, price-earnings ratio, and environmental management systems into a single empirical framework to explain stock price. The study uses secondary data analyzed in Jamovi through hierarchical linear regression. Based on the reported final-model degrees of freedom, the sample comprises 132 firm-year observations from Indonesian listed firms. The findings show that the final model is statistically significant and explains 20.09% of stock-price variation. Profitability is the strongest positive determinant of stock price, while environmental management systems and several board gender diversity categories are negatively associated with stock price. Firm size, shareholders’ equity ratio, and price-earnings ratio are not statistically significant in the full model. The study contributes by integrating conventional financial drivers with governance and sustainability variables in one framework for an emerging market, where prior studies often examine these factors separately. Practically, the results suggest that investors in Indonesia continue to price profitability more strongly than governance or sustainability signals, while firms may still face short-term valuation penalties when sustainability investments or board restructuring are not yet fully appreciated by the market.